Picnic at Hanging Rock - Lindsay, Joan 1896-1984 (Viking, 2012)
'Don't worry about us, Mam'selle dear,' smiled Miranda. 'We shall only be gone a very little while.' But they weren't. By turns eerie, haunting and thrilling, Joan Lindsy's story of vanishing schoolgirls is one of Australia's greatest mysteries. Every so often, there comes a story so brilliant and lively and moving that it cannot be left in the past. Rediscover the magic of our country's most memorable children's books in the Penguin Australia Children's Classics series of stories too precious to leave behind
Keywords: Geschichte 1900-2000; Geschichte 1900; Australian; Schoolgirls / Australia / Juvenile fiction; Private schools / Australia; Picnics / Juvenile fiction; Detective and mystery stories, Australian; Australian literature / 20th century; Australian literature; Picnics; Private schools; Schoolgirls; Studentin; Verschwinden; Ausflug; Australia; Australien; Fiktionale Darstellung